Development and implementation of an automated system of optimal bar cutting at the mill 370/150 at OJSC «BSW – Management Company of the Holding «BMC» - I. A. Pankovets (Литьë и металлургия)
The actual problem of production of long products in bars at the current production of mill 370/150 of OJSC «BSW – Management Company of the Holding «BMC» is considered, a brief technological model of obtaining long products in bars is given, an algorithm for determining the optimal cutting of long products is developed. The developed algorithm will help to reduce the cost of production per one ton and increase the competitiveness of the company’s products. The mechanism of formation of rods of non – dimensional length, which in turn significantly affect the consumption coefficient of metal in production, is revealed.